KERAGAMAN JENIS DAN VARIASI GENETIK CACING TANAH DI KEBUN BIOLOGI UNIVERSITAS GADJAH MADA BERDASARKAN PENANDA MOLEKULAR - , sita ratnawati; , Dr. Niken Satuti Nur Handayani, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Earthworms are one of the invertebrate species which hasnât backbone. The earthworm has more utilized. This Utilized were applicable to degradation of rubbish, Meal of Poultry, matter of medicine, and as a matter of cosmetics. The Earthworm has lived in a few habitats, for example in the humid of forest ground with the high density of cover canopy. Field of Biology UGM is an artificial forest and has a high density of cover canopy and this condition can supported the living habitat of earthworms. The aim of this research were investigated species diversity of earthworm and investigated genetics variation of earthworm in the field of Biology UGM. The eartworms identification base on morphological identification and molecular characterization. Sampling method was carried out with purposive random sampling method. The books of identification were used the earthworm book (Minnich, 1977), Biology of Earthworms (Edwards & Lofty, 1977), dan The Fauna of British India (Stephenson, 1923). Molecular characterization was used RAPD-PCR (Random Amplified Polimorphic DNA- Polymerase Chain Reaction). Result obtained that the earthworms in the field Biology of UGM consist of three species. The Three species were Pheretima hawayana, Pheretima sp., and Eudrilus eugeniae. Data analysis was used UPGMA method by 3.1 MVSP Program and obtained that generally, similarity percentation of P. hawayana, Pheretima sp., dan E. eugeniae interspecies more than 55 %. Whereas Similarity Percentation of P. hawayana and Pheretima sp more than 85 %. The highest value of Genetic variation of eartworms based on polymorphic percentation was Pheretima sp with the value is 80 %, and then overtaken by P. hawayana species with the polymorphic value is 78.57 %, and the last, E. eugeniae with the polymorphic value is 73.68 %. A species of earthworms in the field of Biology UGM has a certain character, and had intra-species variation due to sexual recombination.